2015
DOI: 10.1631/jzus.b1500081
|View full text |Cite
|
Sign up to set email alerts
|

Mutualistic fungal endophytes produce phytohormones and organic acids that promote japonica rice plant growth under prolonged heat stress

Abstract: This study identifies the potential role in heat-stress mitigation of phytohormones and other secondary metabolites produced by the endophytic fungus Paecilomyces formosus LWL1 in japonica rice cultivar Dongjin. The japonica rice was grown in controlled chamber conditions with and without P. formosus LWL1 under no stress (NS) and prolonged heat stress (HS) conditions. Endophytic association under NS and HS conditions significantly improved plant growth attributes, such as plant height, fresh weight, dry weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 32 publications
4
28
0
1
Order By: Relevance
“…In our study, we described a much higher production for the same species. Waqas [60] described IAA production by P. formosus at 34.07 ± 3.92 µg mL −1 , a result very similar to the findings of this study, and consequently, a plant growth-promoting effect. Nevertheless, Waqas [61] analyzed the variability of IAA production as a function of the culture medium used and conversely found that P. variotii had virtually undetectable phosphatase activity.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we described a much higher production for the same species. Waqas [60] described IAA production by P. formosus at 34.07 ± 3.92 µg mL −1 , a result very similar to the findings of this study, and consequently, a plant growth-promoting effect. Nevertheless, Waqas [61] analyzed the variability of IAA production as a function of the culture medium used and conversely found that P. variotii had virtually undetectable phosphatase activity.…”
Section: Discussionsupporting
confidence: 90%
“…It can be used directly or indirectly as a potential biostimulant. When used directly, Paecilomyces or its metabolites increases the plant morphological parameters and crop yield [ 15 , 34 , 35 , 36 , 37 ]. The plant– Paecilomyces interaction improves plant health through different mechanisms and provides protection from phytopathogens [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter may suggest more competition between these fungal pathogens and Xoo in healthy or asymptomatic leaves. However, nonpathogenic strains of Fusarium, Aspergillus, and Phialemoniopsis have been assessed for antagonistic activities against plant pathogens including F. oxysporum, Colletotricum gloeosporioides, and Sclerotium rolfsii (Tayung and Jha, 2010;Waqas et al, 2015;Mastan et al, 2019). Therefore, it may be worthwhile to further isolate and determine the identity and virulence of these fungal strains.…”
mentioning
confidence: 99%